Formulation and evaluation of controlled release floating microspheres of tolperisone hydrochloride - Jani, Pooja; Vadalia, Kantilal; Bagdai, Hiral; Dedania, Ronak; Manseta, Paresh (Asian Journal of Pharmaceutics (AJP), 2014)
Main aim of this study was to develop controlled release (CR) floating multiparticulate drug delivery system of tolperisone hydrochloride. Microspheres were prepared by nonaqueous solvent evaporation technique consisting of porous calcium silicate (Florite or FLR) as porous carrier, tolperisone hydrochloride (API), Ethyl cellulose (EC), and HPMC 15 cPs as rate controlling polymers. 23 full factorial design was applied for optimization of formulation. The effect of various formulation and process variables on the particle morphology, micromeritic properties, in vitro floating behavior, entrapment efficiency, and in vitro drug release were studied. The size of microspheres was varied from 300 to 500 Î¼m. The microspheres were found to be highly porous and regular in shape. All the formulations showed excellent flow properties. The percentage entrapment efficiency of all batches was greater than 80%. The percentage buoyancy varied from 85% to 98% at the end of 12 h. The release rate was determined in simulated gastric fluids. The formulation demonstrated favorable in vitro floating and release characteristics. Different kinetic models were applied to study the release mechanism. All formulations followed Higuchi model, which indicates the diffusion control release of water soluble drug from polymer matrix. Multiple regression analysis was applied for study of the effect of independent variables on the dependent variables.